Revisioning Juvenile Justice: Implications of the New Child Protection Movement - Levesque, Roger J. R. (1995)
This Article examines the soundness of the new family and community based juvenile justice system. Part I examines the punitive zeitgeist that has developed within the juvenile justice system. Part II then examines juveniles' legal rights to in-home services and concludes that while juveniles may not have an affirmative right to in-home services, they do have liberty interests that protect against unnecessary removals from their homes. Part I details the reasons for directing efforts and resources to support family-based services for delinquent youth. This section explores the problems with current out-of-home placements, policy concerns favoring in-home placements, and the cost-benefit effectiveness of in-home placement programs. Part IV then provides an overview of the new family preservation statutes. These statutes highlight the often self-defeating effect of defamilization and state legislatures' interests in nonpunitive approaches to children who require state intervention. Finally, Part V concludes that the new child protection movement should not ignore delinquent youth and cautions against creating the type of boilerplate statutes that have historically plagued the juvenile justice system